Metal-free photochemical silylations and transfer hydrogenations of benzenoid hydrocarbons and graphene - Raffaello Papadakis (Nature Portfolio, 2016)
Baird’s rules say that the first triplet state of benzene displays antiaromatic character. Here, the authors exploit this to show that aromatic molecules can undergo rapid transfer hydrogenation or silylations without the need for metal catalysts when photochemcially excited into this state.